2021
DOI: 10.3390/ani11010122
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Red Light on Mammalian Sperm Rely upon the Color of the Straw and the Medium Used

Abstract: Previous research has determined that irradiation of mammalian sperm with red light increases motility, mitochondrial activity, and fertilization capacity. In spite of this, no study has considered the potential influence of the color of the straw and the extender used. Therefore, this study tests the hypothesis that the response of mammalian sperm to red light is influenced by the color of the straw and the turbidity/composition of the extender. Using the horse as a model, 13 ejaculates from 13 stallions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The wavelength of the light seems be an important element in the cascade of changes that lead to mitochondrial ROS generation. Thus, a brief (<5 min) exposure to red light (620–630 nm) was found to stimulate sperm motility and ROS generation by equine and, to a much less extent, ram spermatozoa [ 98 ]. Similarly, red light (maximum energy at 600 nm) has been found to stimulate ROS generation in populations of human spermatozoa, which responded by exhibiting a burst of hyperactivated motility and associated shifts in intracellular calcium and cAMP [ 99 ].…”
Section: Sources Of Ros In the Human Ejaculatementioning
confidence: 99%
“…The wavelength of the light seems be an important element in the cascade of changes that lead to mitochondrial ROS generation. Thus, a brief (<5 min) exposure to red light (620–630 nm) was found to stimulate sperm motility and ROS generation by equine and, to a much less extent, ram spermatozoa [ 98 ]. Similarly, red light (maximum energy at 600 nm) has been found to stimulate ROS generation in populations of human spermatozoa, which responded by exhibiting a burst of hyperactivated motility and associated shifts in intracellular calcium and cAMP [ 99 ].…”
Section: Sources Of Ros In the Human Ejaculatementioning
confidence: 99%
“…Although, under a practical point of view, getting new insights into how light exerts the aforementioned effects could improve in vivo reproductive efficiency, the mechanisms underlying that response remain largely unknown. In addition, previous research has demonstrated that the sperm response to light depends on other factors, including the species, nature of semen (i.e., fresh, frozen-thawed), wavelength range and color of the recipient/straw (Catalán et al, 2020a;Catalán et al, 2020b;Blanco-Prieto et al, 2020;Catalán et al, 2020c;Catalán et al, 2020d;Catalán et al, 2021). In the case of pigs, different studies reported inconsistent results, as whereas Luther et al (2019) found an impairment of sperm function, others observed a positive impact on sperm quality and fertilizing ability (Yeste et al, 2016;Blanco-Prieto et al, 2019;Pezo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%